Exploring Subjective Perception of Safety in Public Spaces in Serbia: Insights from the European Social Survey - Marković, Aleksandra; Filipović, Božidar (NBP. Nauka, bezbednosti, policija, 2024)
The perception of safety plays a crucial role in shaping individuals’ interactions with their environment and can have significant implications for the prevalence and persistence of criminal activity within communities. Perceived unsafety can lead individuals to fear becoming victims of crime and can affect the willingness of individuals to report crimes to authorities. Furthermore, it can undermine social cohesion within communities by eroding trust and cooperation among residents. The subjective safety experience in public spaces is a multifaceted phenomenon influenced by various determinants. Using data from the European Social Survey Round 10, the paper aims to scrutinise the potential factors contributing to feelings of safety among respondents in Serbia. We focus on respondents’ perceptions of safety in four regions (Belgrade, Vojvodina, Šumadija and West Serbia, and South and East Serbia) operationalised through the question "How safe do you – or would you - feel walking alone in your neighbourhood after dark?". By examining determinants such as age, gender, daily activity, area (rural or urban), social capital, interpersonal trust and perceived quality of society, this paper aims to shed light on the complexities of safety perception. The primary findings underscore the significance of individual vulnerability and social integration measures as critical indicators of safety perceptions in public spaces. The study highlighted notable regional variations in predictors of safety perceptions, emphasising the necessity of localised approaches to address safety concerns. By comprehensively understanding the determinants of subjective safety, policymakers and urban planners can develop targeted strategies to mitigate fear and enhance safety perceptions.